Somatic symptom profile in patients with chronic heart failure with and without depressive comorbidity - Müller-Tasch, Thomas; Löwe, Bernd; Frankenstein, Lutz; Frey, Norbert; Haass, Markus; Friederich, Hans-Christoph (Frontiers in Psychiatry, 2024)
Patients with chronic heart failure (CHF) frequently suffer from depressive comorbidity. CHF and depressive comorbidity can cause somatic symptoms. The correct attribution of somatic symptoms is important. Thus, we aimed to assess potential differences in somatic symptom severity between CHF patients with and without depressive comorbidity.We evaluated depressive comorbidity using the Patient Health Questionnaire-9 (PHQ-9), somatic symptom severity with the Patient Health Questionnaire-15 (PHQ-15), and sociodemographic and medical variables in 308 CHF outpatients.To compare somatic symptom severity between CHF patients with and without depressive comorbidity, we conducted item-level analyses of covariance.Of the 308 participating patients, 93 (30.3%) met the PHQ-9 criteria for depressive comorbidity. These patients did not differ from those without depressive comorbidity with regard to age, sex, left ventricular function, and multimorbidity. Patients with depressive comorbidity scored significantly higher on ten out of thirteen PHQ-15 items than patients without depressive comorbidity.The largest effect sizes (0.71-0.80) were shown for symptoms of headache, chest pain, shortness of breath, and palpitations, and the latter three were potentially attributable to heart failure.Among patients with CHF, somatic symptoms are more pronounced in those with depressive comorbidity than those without depressive comorbidity. This finding is especially true for cardiac symptoms independent of CHF severity. The potential interpretation of somatic symptoms as correlates of depressive comorbidity must be recognized in clinical practice.